(untitled) (CAHIERS MAGELLANES-NS, 2024)
This project in Computer Science and Engineering aims to empower parents by providing real-time location tracking for school buses. It addresses the need for ensuring children's safety during their commute. The project utilizes technology to offer parents peace of mind by allowing them to monitor the whereabouts of school buses in real-time. Through the integration of GPS tracking and mobile applications, parents can conveniently track the location of their children's buses, receive timely updates, and ensure their safe arrival to and from school. This initiative not only enhances parental confidence but also promotes overall safety and efficiency in school transportation systems.Ensuring the safety and security of children during their commute to and from school is of utmost importance. Leveraging advancements in Internet of Things (IoT) technology and Radio Frequency Identification (RFID), this paper presents the design and implementation of a low-cost system aimed at providing real-time tracking and monitoring capabilities for children traveling via school buses or private vehicles. The system offers a comprehensive solution for families, schools, and authorities to enhance the safety of children during their transportation, addressing critical concerns in today's educational landscape.